Entropy Profiling for the Diagnosis of NCA/Gr-SiOx Li-Ion Battery Health. Issue 10 (1st October 2022) - Wojtala, Malgorzata E.; Zülke, Alana A.; Burrell, Robert; Nagarathinam, Mangayarkarasi; Li, Guanchen; Hoster, Harry E.; Howey, David A.; Mercer, Michael P.
Abstract : Graphite-silicon (Gr-Si) blends have become common in commercial Li-ion battery negative electrodes, offering increased capacity over pure graphite. Lithiation/delithiation of the silicon particles results in volume changes, which may be associated with increased hysteresis of the open circuit potential (OCP). The OCP is a function of both concentration and temperature. Entropy change measurement—which probes the response of the OCP to temperature—offers a unique battery diagnostics tool. While entropy change measurements have previously been applied to study degradation, the implications of Si additives on the entropy profiles of commercial cells have not been explored. Here, we use entropy profiling to track ageing markers in the same way as differential voltage analysis. In addition to lithiation/delithiation hysteresis in the OCP of Gr-Si blends, cells with Gr-Si anodes also exhibit differences in entropy profile depending on cycling direction, reflecting degradation-related morphological changes. For cycled cells, entropy change decreased during discharge, likely corresponding to graphite particles breaking and cracking. However, entropy change during charge increased with cycling, likely due to the volume change of silicon. Over a broad voltage range, these combined effects led to the observed rise in entropy hysteresis with age. Conversely, for calendar aged cells entropy hysteresis remained stable.